Electronic Word-of-Mouth and Patient Satisfaction in Hospital Services: A Systematic Literature Review and Bibliometric Analysis - Emawan Noor Fikri; Safari Wahyu Jatmiko; Anton Agus Setyawan (Universitas Muhammadiyah Malang, 2026)
This study aims to identify the factors influencing electronic word-of-mouth (e-WOM) and assess its impact on healthcare services. This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, along with a bibliometric analysis to develop research on electronic word-of-mouth and satisfaction with hospital services. Article searches were conducted in the PubMed and Lens databases for the years 2015–2024 using the SPICE strategy. Out of 443 articles found, n =112 met the criteria for further analysis. At the beginning of 2015, the publication trend was 6 documents, peaking in 2022 with 44 documents. Based on the VOSviewer analysis, the keyword “humans” appeared most frequently, 41 times, followed by “social media” 23 times. “Male” and “female” each appeared 19 times. The frequency of keyword occurrences in previous research is reflected in 34 articles published during the 2000–2019 period, while the effect size of e-WOM in hospitals shows that the Assurance dimension of SERVQUAL has the highest negative impact (58.3%), followed by Responsiveness (34.2%). The theoretical implication of this article is that e-WOM has a positive impact on satisfaction, image, service choice decisions, and patient loyalty, suggesting that hospitals should manage it effectively and adjust strategies based on patient demographics. The managerial implication is that hospitals need to leverage e-WOM to improve service quality and patient engagement by promoting positive experiences, implementing loyalty programs, pursuing continuous service improvement, using AI-based digital innovations, and analyzing social media to enhance communication and build a supportive patient community. In conclusion, these findings provide strategic insights for hospital managers on strengthening patient loyalty through e-WOM optimization.